2017
DOI: 10.1016/j.jece.2017.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of extraction and in situ transesterification of oils from spent coffee grounds

Abstract: Resource limits, environmental concerns and unstable petroleum costs have led to an increased effort to develop alternative liquid fuels. Purpose grown feedstocks are expensive and demand additional resources such as land and water. Spent coffee grounds (SCGs) are a good potential low-cost feedstock, however, processing times and costs must be lowered in order to be cost competitive with fossil fuels.In this work, we investigated the kinetics of oil extraction from SCGs to explore if current methods of oil ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 35 publications
2
11
2
Order By: Relevance
“…It is important to note that the oil content of BSGs ranges from 3.9% to 13.3% on dry bases [the same as above??] which is comparable with the oil content found in the other feedstocks such as 20% in Jatropha curcas (Sinha et al, 2015), 14% in spent coffee grounds (Najdanovic-Visak et al, 2017) and other agricultural waste including seeds of tea, tobacco or tomato, linseed and bay laurel leaves (Rehan et al, 2017).…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…It is important to note that the oil content of BSGs ranges from 3.9% to 13.3% on dry bases [the same as above??] which is comparable with the oil content found in the other feedstocks such as 20% in Jatropha curcas (Sinha et al, 2015), 14% in spent coffee grounds (Najdanovic-Visak et al, 2017) and other agricultural waste including seeds of tea, tobacco or tomato, linseed and bay laurel leaves (Rehan et al, 2017).…”
Section: Introductionsupporting
confidence: 77%
“…However, decrease in the yield was observed with further increase of the ratio (Fig.6). This trend is well documented to other in situ transesterification, such as that from the spent coffee grounds (Najdanovic-Visak et al, 2017) and from Jatropha curcas (Kasim and Harvey, 2011). Initial yield increase is due to higher concentration of methanol favouring the biodiesel production while further increase in amount of methanol dilutes triglycerides leading to lower reaction rates.…”
Section: In Situ Transesterificationsupporting
confidence: 68%
See 1 more Smart Citation
“…It is generally reported that the extraction rate increases with increasing temperature and liquid/solid ratio, and decreasing particle size; however, these parameters shall be extensively studied, since high temperatures may favor the extraction yield of solids and disfavor the recovery of phenolic compounds and antioxidants (Torun et al, 2015). Earlier works reported the extraction efficiency of different coffee species by using different extraction methods, such as, conventional (n-hexane, water, anhydrous and hydrous ethanol, methanol and their mixtures) (Bravo et al, 2013;Najdanovic-Visak et al, 2017;Somnuk et al, 2017), pressurized liquid (water, ethanol, and methanol) (Belandria et al, 2016;Oliveira et al, 2018), ultrasound assisted (ethanol) (Al-Dhabi et al, 2017), supercritical CO 2 (De Marco et al 2018;Getachew et al, 2018), and microwave extraction (petroleum ether) (Tsukui et al, 2014). However, there is no reported study on the organic solvent extraction behavior of total soluble solids from green coffee beans and its press cake in order to state the feasibility of mechanical oil extraction.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the material containing the oil is kept in direct contact with the reagent acting in both the extraction and the reaction. [ 9–12 ] The use of this integrated process (extraction followed by reaction) eliminates the need for separation, oil purification and solvent recovery and significantly reduces the processing time. [ 13,14 ] The elimination of these steps allows the overall process of biodiesel production to be simplified, making it economically attractive.…”
Section: Introductionmentioning
confidence: 99%